Brucein D imparts a growth inhibitory effect in multiple myeloma cells by abrogating the Akt‐driven signaling pathway. Issue 2 (2nd November 2022) - Jung, Young Yun; Mohan, Chakrabhavi Dhananjaya; Rangappa, Shobith; Um, Jae‐Young; Chinnathambi, Arunachalam; Alharbi, Sulaiman Ali; Rangappa, Kanchugarakoppal S.; Ahn, Kwang Seok
Abstract: The Akt signaling pathway is an oncogenic cascade activated in the bone marrow microenvironment of multiple myeloma (MM) cells and contributes to their uncontrolled proliferation. Abrogation of Akt signaling has been presented as one of the prime therapeutic targets in the treatment of MM. In the present report, we have investigated the effect of Brucein D (BD) on Akt‐driven signaling events in MM cells. BD (300 nM) substantially inhibited cell viability and imparted growth‐inhibitory effects in U266 cells as evidenced by cell viability assays and flow cytometric analysis. Effect of BD on cell viability was evaluated by MTT assay. Apoptotic cells and cell cycle arrest by BD were analyzed by flow cytometer. The results of the TUNEL assay and western blotting showed that BD induces apoptosis of MM cells by activating caspase‐8 and 9 with subsequent reduction in the expression of antiapoptotic proteins (Bcl‐2, Bcl‐xl, survivin, cyclin D1, COX‐2, VEGF, MMP‐9). Analysis of activated kinases by Phospho‐Kinase Array Kit revealed that Akt, p70S6K, HSP60, p53, and WNK1 were strongly expressed in untreated cells and BD treatment reversed this effect. Using transfection experiments, AKT depletion led to a decrease in phosphorylation of Akt, mTOR, p70S6K, and WNK. However, Akt overexpression led to increase in phosphorylation of these proteins. Depletion of Akt potentiated the apoptosis‐inducing effect of BD whereas overexpression displayed resistance to BD‐induced apoptosis suggesting the role of Akt in chemoresistance. Taken together, BD mitigates Akt‐dependent signaling pathways in MM cells to impart its anticancer activity.